Review of the synthesis, characterization and application of zirconia mixed metal oxide nanoparticles - Precious Ayanwale, Ayodeji (2018)
There has been different synthetic route used for the synthesis of zirconia mixed metal oxide nanoparticles. The different synthetic methods coupled with other factors like concentration, PH, type of precursor used etc help to synthesize zirconia mixed metal oxide nanoparticles having different physicochemical properties. This paper discusses the different synthetic routes of sol-gel, hydrothermal and coprecipitation method for the formation of zirconia in combination with other metal oxide to form zirconia mixed metal oxide nanoparticles, the physicochemical properties of the synthesized zirconia mixed metal oxide nanoparticle, their characterization and application.